2019
DOI: 10.1038/s41598-019-45652-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of nitrite acting as a stable and robust inducer of non-cultivability in Mycobacterium tuberculosis with physiological relevance

Abstract: Tuberculosis (TB) is the ninth leading cause of death worldwide, ranking above human immunodeficiency virus. Latency is the major obstacle in the eradication of this disease. How the physiology of the pathogen changes in transition to the latent stage needs to be understood. The latent bacteria extracted from animal hosts exist in a nonculturable (NC) phase, whereas bacteria extracted from most in vitro models are culture-positive. In the present study, we observed that nitrite, up to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 61 publications
1
10
0
1
Order By: Relevance
“…Growth is the important characteristic features of the active state of mycobacteria. In our earlier report we have seen that nitrite induces VBNC state by inhibiting the growth of Mtb cells 24 . In order to correlate the effects of varying NO level on the development of non-/replicating status of Mtb bacilli when the growth of KDnirK Mtb strain was measured in presence of nitrite under conditions of w/o antibiotic induction (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Growth is the important characteristic features of the active state of mycobacteria. In our earlier report we have seen that nitrite induces VBNC state by inhibiting the growth of Mtb cells 24 . In order to correlate the effects of varying NO level on the development of non-/replicating status of Mtb bacilli when the growth of KDnirK Mtb strain was measured in presence of nitrite under conditions of w/o antibiotic induction (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…8 ). The two independent experimental results clearly showed that in ATc induced KDnirK cells grow even in the presence of nitrite (10 mM) whereas the growth was inhibited when the culture is not induced by the antibiotic 24 . This clearly proved that knockdown has successfully been executed on the expression of nirK and the role of the gene is observed in converting nitrite to NO within the cell.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Exposure of mycobacteria to reactive nitrogen species lowers CFU counts [17,28,29], which could indicate the presence of DCB. Mtb incubation with acidified nitrite in 7H9 medium at concentrations above 5 mM reduced Mtb CFU counts, but resuscitation in liquid medium was not achieved (Fig.…”
Section: Design Synthesis and Testing Of A Novel No Donormentioning
confidence: 99%
“…for the diagnosis of TB. In addition, bacterial plasticity and mechanisms leading to latency result in loss of culturability 44,45. Difficulties in obtaining an adequate tissue biopsy from various affected areas without causing further damage to the female genital tract makes endometrial tissue the most widely used source for bacteriological diagnosis of FGTB 38,41.…”
mentioning
confidence: 99%